Match making in complex social networks - Mao, Fubing (2021)
Match making is of significant importance in some social systems. People may need to seek for romantic partners, teammates, collaborators, etc. In this paper, we propose a minimalist framework of match making in complex networks. Specially we adopt a simple model where each individual would greedily seek for making a match with the strongest partner within his/her social connection range. We explore a few matching schemes including greedy mode, roulette wheel selection mode and completely random mode on different networks. We also investigate when social systems become more densely connected, how the match making process would be affected. Our observations show that, in a more densely connected social network, individuals’ efforts for seeking for matches with the strongest partners would be more likely to end up with matching with someone similar to themselves. Meanwhile, the cost of such an approach may be quickly increased. The implications of such observations in real-life systems and open problems are briefly discussed.